Pengaruh Literasi Digital, Motivasi Belajar dan Berpikir Kreatif terhadap Prestasi Belajar Matematika Siswa SMP Negeri 3 Wamena - Murip, Dorli; Sembiring, Maximus Gorky; Ramdhani, Sendi; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2024)
: This study aims to identify the influence of digital literacy, learning motivation, and creative thinking on students' mathematics learning achievement. The sample of this study was 50 students of class VIII of SMP Negeri 3 Wamena. Data collection includes digital literacy questionnaires, learning motivation, and creative thinking written test questions, as well as documentation of mathematics scores. The results of the regression analysis showed a positive relationship between the independent variables and the dependent variables with a Multiple R-value of 0.3065, still only 9.39% of the variation in mathematics learning achievement can be explained by the three independent variables (R Square = 0.0939), the smaller the Adjusted R Square of 0.0348 indicates that this model has low predictive power. X1 (digital literacy) and X2 (learning motivation) are not significant to mathematics learning achievement with p-values ​​of 0.315 and 0.430 respectively, indicating that both do not affect mathematics learning achievement, on the other hand, X3 (creative thinking) with a p-value of 0.055 approaching the significance limit which means that the possibility of its influence is more significant. This study suggests the need for a more in-depth approach to other factors that contribute to students' mathematics learning achievement.